Pengujian Beberapa Formulasi Trichoazolla terhadap Pertumbuhan Bibit Kelapa Sawit di Pembibitan - Wahyudi, Cecep Ijang; Puspita, Fifi (Jurnal Agro Teknologi Tropika, 2014)
This study aimed to investigate the effect and get better interaction from the oil palm crosses and formula ofTrichoazolla to the growth of oil palm seedlings in nursery. Research conducted experimentally using FactorialRandomized Block Design with 2 factors and repeated three times. Data were analyzed statistically by analysis ofvarience and data showing the real effect was tested further by Duncanâs New Multiple Range Test (DNMRT) at 5%. Theresults showed that the formula of Trichoazolla compost and crosses of oil palm interact positively about increaseheight, wet weight, dry weight, crown root ratio and root volume of oil palm seedlings. The main effect of oil palm crossescan trigger plant growth through accretion high, number of leaves, wet weight, dry weight, rod diameter, crown rootratio and root volume of oil palm seedlings. The main effect of Trichoazolla formulations affect of height increment, thenumber of leaves, wet weight, dry weight, rod diameter, crown root ratio and root volume of oil palm seeds.Keywords : Trichoazolla formulation, oil palm, nursery